The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.3138/ecf.24.3.403
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking Gender and Virtue through Richardson's Domestic Accounting

Abstract: A formal approach to the history of the novel is illuminative when form itself becomes a marker of virtue, a term at the heart of the so-called “Pamela controversy,” whose respondents doubt the virtue of Pamela's accounts. Analyzing the ways in which Samuel Richardson uses the formal components of the account in Pamela helps us to understand just what is at stake in the Pamela controversy. The changes Richardson makes in Clarissa, including proliferating points of view in order to help the reader to trust Clar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Progressive ideology targets the rapprochement between members of different stratification and the possibility of their convergence and marriage that entails social mobility when someone elevates his or her social class and demands inclusion in the new social circle. Roxburgh (2012) supposes that Pamela's comportment of rejecting Mr. B.…”
Section: Discussionmentioning
confidence: 99%
“…Progressive ideology targets the rapprochement between members of different stratification and the possibility of their convergence and marriage that entails social mobility when someone elevates his or her social class and demands inclusion in the new social circle. Roxburgh (2012) supposes that Pamela's comportment of rejecting Mr. B.…”
Section: Discussionmentioning
confidence: 99%
“…In Clarissa , the heroine is prepared for the role of estate manager as her accounting skills are praised by both her grandfather and her uncle (Richardson, 2004, 1414, 155; Richardson, 1751, 8.205).Clarissa’s will follows the structure of an inventory that carefully accounts for all the items in the estate, including the sum ‘accrued from that estate since my grandfather’s death’ and ‘all the family pictures’ (Richardson, 2004,1414). Natalie Roxburgh has shown that the practice of keeping an account book became part of women’s education and was associated with the ability to account for oneself economically and spiritually (Roxburgh, 2012, 403–429). Clarissa´s view of the inheritance focuses on the responsibility and duty involved.…”
Section: Clarissa’s Willmentioning
confidence: 99%
“…"Rethinking Gender and Virtue through Richardson's Domestic Accounting" (Roxburgh, 2012). In her article, Roxburgh presents a unique analysis of Samuel Richardson's novel Pamela by examining the representation of domestic accounting in the story.…”
mentioning
confidence: 99%